The subject of objects: Marx, new materialism, & queer forms of life. Issue 2 (3rd April 2018) - Cole, Alyson
Abstract: This article examines two interrelated themes in the scholarship categorized as 'new materialism': first, the aim to undermine the subject/object distinction; second, the proposition that agency exists across the material world. While new materialists, such as Jane Bennett, conceive of their approach as an intervention against the injurious effects of capitalism, I argue that destabilizing the object/subject binary and endowing inanimate objects with vitality and agency is actually a constitutive feature of capitalism itself. To illustrate this point, I turn to Marx's analysis, providing a queer reading of his theorization of commodities. Revisting Marx's account of commodity fetishism in tandem with new materialism yields fresh insights into the logics of capitalism, specifically, the manner in which it thrives on concurrently producing and erasing subjectivities, thereby distorting social materiality and material sociality.